Investigation of Factors Influencing Dispersion of Liquid Hydrocarbons in Porous Media (Journal of Engineering, 2016)
An experimental work has been done to study the major factors that affect the axial dispersion of some hydrocarbons during liquid-liquid miscible displacement. Kerosene and gas oil are used as displacing phase while seven liquid hydrocarbons of high purity represent the displaced phase, three of the liquids are aromatics and the rest are of paraffinic base. In conducting the experiments, two packed beds of different porosity and permeability are used as porous media.The results showed that the displacement process is not a piston flow, breakthrough of displacing fluids are shown before one pore volume has been injected. The processes are stable with no evidence of viscous fingering.Dispersion model as adapted by Brigham et.al (1961) is used to determine the axial dispersion coefficient of displacing fluid. The results show an increasing in dispersion coefficient as the interstitial velocity and viscosity ratio increases.